Supply Chain Strategy in Initial Public Offering in Malaysia: A Review of Long-run Share Price Performance - Abbas Almtoor, Yasir Abdullah; Ahmad Zaluki, Nurwati Ashikkin; Abd Rahim, Nazahah (ExcelingTech Publishers, 2019)
The paper examined the current status of research regarding the long-run share price performance of initial public offerings (IPO) in Malaysia. The review on previous studies was divided into the followings: underwriter reputation, earnings management, and board variables .The paper found that there was a noticeable poor long-run performance, and Malaysian IPOs were lesser than others from developed nations. The evidences of the long-run performance were inconsistent. This paper pinpointed significant factors that could the influence long-run share price performance in the Malaysian IPO market. New areas for future research were also suggested